Marriage Migration and the Labour Market: 'The case of migrants of Turkish descent in Belgium' - Christiane Timmerman; Johan Wets (Nordic Journal of Migration Research, 2011)
This article starts by asking whether economic motivations can explain why so many youngsters with a migrant background choose to marry a relatively unknown partner from the same region as their parents came from, a region that is largely unknown to them, and conversely why so many young people in countries in the South are opting for an unknown partner living in a far away country. In answering these questions Turkish marriage migration to Belgium will be used as a case study, since it offers several helpful insights in understanding the dynamics of marriage migration. The main focus of this article is on the relevance of socioeconomic explanations in understanding this issue. Economic reasons obviously play a role, but it is clear that they alone do not fully explain this phenomenon. The case described shows that reasons for migration go beyond economic benefits, permitting the conclusion that the popularity of marriage migration can only be explained by taking multiple frames of reference into account. Given the poor prospects and poor labour market situations for Turkish migrants, economic motivation seems an insufficient explanation of the phenomenon. It is clear that the existence of a "culture of migration" that binds the region of origin with the region of destination, one in which "the family" as an institution is capable of bridging the traditional praxis and the challenges linked to international migration, is complementary to understanding the enduring popularity of marriage migration between Emirdağ and Flanders.